Bakti Sosial Di Panti Asuhan Istana Yatim Al-Jufri - Stella Stella; Oktavina Oktavina; Evelyn Evelyn; Jennifer Jennifer; Kelvin Carrie; Joviki Rahman; Kelvin Kelvin; Azhar Maulana (National Conference for Community Service Project (NaCosPro), 2019)
As we study higher education, the least we can do is contribute back to society. We need to apply the rule of “ Give and Take”. Inspired by our lecturer giving us support and encouragement. We, eight people, decided to visit an orphanage called “Panti Asuhan Istana Yatim Al-Jufri” which located at sekupang as our class’s devotion target is in this area. We donate things such as food & drink, snack, stationery stuff and teaching the kids mandarin language based on our ability. We believe that even though we are not giving them much, but it’s better than no. right ? Seeing the kids smile and laughing is the best satisfaction we get from this implementation program. It may sounds like there’s no innovation, we do admit that. However, we thought that the outcome we get is far more important than innovation that we don’t even have any ideas.